Low‐energy ion precipitation structures associated with pulsating auroral patches. Issue 7 (14th July 2015) - Liang, Jun; Donovan, E.; Nishimura, Y.; Yang, B.; Spanswick, E.; Asamura, K.; Sakanoi, T.; Evans, D.; Redmon, R.
Abstract: Pulsating auroras often appear in forms of geo‐stable or slowly convecting "patches." These patches can maintain their rough shape and size over many sequences of luminosity pulsations, yet they slowly drift with ionospheric E × B convection. Because of these characteristics, there has long been a speculation that the pulsating auroral patch (PAP) is connected to flux tubes filled with enhanced cold plasma. In this study, we perform a survey on pulsating auroral events when the footprints of low‐Earth‐orbit satellites traversed the PAPs, with a focus on the low‐energy particle signatures associated with the PAPs. As a result, we identified, in a majority ( 2/3) of events, the existence of a low‐energy ion precipitation structure that is collocated with the PAP, with core energies ranging from several tens of eV up to a few hundred eV. This result supports the hypothesis that a PAP connects to flux tubes filled with enhanced cold plasma. We further propose that the plasma outflows from the ionosphere are the origin of such cold plasma flux tubes. We suggest that the PAP is formed by a combination of high‐energy electrons of a magnetospheric origin, the low‐energy plasma structure of an ionospheric origin, and certain ELF/VLF waves that are intensified and modulated in interactions with both the hot and cold plasma populations. Key Points: Colocation of low‐energy ion structure and pulsating auroral patch Pulsating auroral patches connect to flux tubes filled with enhanced cold plasma Plasma outflows from ionosphere as the origin of cold plasma flux tubes